2021
DOI: 10.1093/ajhp/zxab296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rapid methicillin-resistant Staphylococcus aureus nasal polymerase chain reaction screening on vancomycin use in the intensive care unit

Abstract: Purpose To determine the impact of a pharmacist-driven methicillin-resistant Staphylococcus aureus (MRSA) nasal polymerase chain reaction (PCR) screen on vancomycin duration in critically ill patients with suspected pneumonia. Methods This was a retrospective, quasi-experimental study at a 613-bed academic medical center with 67 intensive care beds. Adult patients admitted to the intensive care unit (ICU) between 2017 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…19,20 Although these findings are similar to our study, the most common pneumonia classification in Raush et al 19 was CAP and most patients received linezolid or ceftaroline as anti-MRSA therapy. Our study found more patients with HAP and receiving vancomycin, which is more consistent with the findings from Diep et al 20 In addition, Diep et al 20 did not report any critical care scoring systems to grade the severity of illness. Our study only included critically ill patients, with a mean APACHE II score of approximately 17, indicating a 25% nonoperative mortality rate.…”
Section: Discussionsupporting
confidence: 89%
“…19,20 Although these findings are similar to our study, the most common pneumonia classification in Raush et al 19 was CAP and most patients received linezolid or ceftaroline as anti-MRSA therapy. Our study found more patients with HAP and receiving vancomycin, which is more consistent with the findings from Diep et al 20 In addition, Diep et al 20 did not report any critical care scoring systems to grade the severity of illness. Our study only included critically ill patients, with a mean APACHE II score of approximately 17, indicating a 25% nonoperative mortality rate.…”
Section: Discussionsupporting
confidence: 89%
“…In our study of pediatric patients hospitalized for a presumed infectious diagnosis and started on empiric broad-spectrum antimicrobial treatment including anti-MRSA antibiotics, an MNS test, when correlated with clinical cultures, was found to have a high NPV for a clinical MRSA infection. Similar to previous analyses in adults that are promoting MNS as a potentially powerful stewardship tool for de-escalation and avoidance of empirical anti-MRSA therapy [3][4][5][6][7], our findings suggest that MNS could also be a useful tool in limiting anti-MRSA antimicrobials in pediatric patients.…”
Section: Discussionsupporting
confidence: 86%
“…In adult studies, the downstream effects of avoiding or stopping anti-MRSA antibiotics early because of a negative MNS have been manifold, including decreased length of anti-MRSA antibiotics, fewer drug-monitoring labs, decreased nephrotoxicity, and decreased length of stay [ 3 , 4 , 5 ]. In this context, we took great interest to see that the decision to discontinue the anti-MRSA antimicrobial treatment was supported by a negative MNS alone, or by a negative MNS in combination with a negative clinical culture in a quarter and about a third of those children in whom treatment was stopped during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations